Environmental crisis: The missing dimension in the north-south dialogue - Udo E. Simonis (Wissenschaftszentrum Berlin (WZB); Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1984)
At a time when environmental policies in industrialized countries are beginning to prove successful, the growing ecological crisis in developing countries is progressively becoming a problem of worldwide significance. Although our earth can and should be understood to be a single homogeneous ecosystem, from the standpoint of environmental policies it is moving increasingly towards structural heterogeneity. This paper outlines the extent and dynamics of the ecological crisis in developing countries, and demonstrates, with relevant examples, its repercussions for the industrialized countries. The presumably mutual interests in preventing or alleviating these negative repercussions are examined. In conclusion, the author recommends taking a telescopic view of the environmental problems and calls for an early recognition of the interdependencies between ecology and economy in the North- South context. – – Je erfolgreicher die Umweltpolitik in den Industrielandern wird, um so mehr wird die fortschreitende Umweltkrise in den Entwicklungslandern fur die Welt insgesamt bedeutsam. Obwohl die Welt als homogene ökologische Einheit begriffen werden kann und rauß, wird sie umweltpolitisch zunehmend heterogen. Im vorliegenden Beitrag werden Ausmaß und Dynamik der Umweltkrise in den Entwicklungsländern skizziert, und es wird - exernplarisch - die Frage gestellt nach den Riickwirkungen auf die Industrielander, d.h. nach gemeinsamen Problemen und den möglichen gemeinsamen Interessen an ihrer Vermeidung und Behandlung. Der Beitrag endet mit einern Plädoyer für eine teleskopische Problembetrachtung, d.h. ein frühzeitiges Erkennen der interdependenten Zusammenhänge von Ökologie und Ökonomie im Nord-Süd-Kontext.
Keywords: 300